Kesulitan Guru dalam Menerapkan Kurikulum Merdeka pada Pembelajaran di Kelas IV SDN Sungai Kuini 2 - Miftahul Jannah (PT. Global Pustaka Ilmiah, 2024)
This study also aims to understand the factors causing these difficulties, their impact on the learning process, and to find solutions or ways that can help teachers overcome obstacles in implementing the independent curriculum in schools. The type of research used is a descriptive qualitative method. The data sources used are interview methods and documentation studies, so that primary data sources and secondary data sources will be obtained. Data analysis was carried out by means of data reduction, data display, and drawing conclusions or data verification (conclusion drawing/verification). The results of this study indicate that there are changes regarding the preparation, implementation and assessment of learning in the independent-based education program. The challenges for educators in implementing independent education in classroom learning include limited facilities and means available, limited teacher ability in preparing examples, difficulties in implementing separate learning in one class, difficulties in implementing the Pancasila Strengthening Student Profile Task (P5), student limitations in completing assessments. learning, and the challenges of educators in collecting it include student learning outcomes for one semester. The implementation of the Independent Learning Education plan for grade IV students has gone quite well.